Improving Student Internalization of Disaster Knowledge by Participating in Learning Package Development - Rina Suryani Oktari; Intan Dewi Kumala (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2020)
In the subject of disaster education, it is crucial to establish a practical approach to give an impactful impression for the student so that it can increase self-awareness as well as for it to be applicable in daily life and memorized longer in each individual. This community services program titled "Development of Learning Packages by and for Students towards a Smart and Resilience Generations in dealing with Disaster." aims at developing creative and innovative disaster education learning packages that meet the needs and characteristics of students. This activity was carried out using a participatory method, through three (3) stages, namely: i) design phase, ii) production stage, and iii) evaluation phase. This activity adopts the experiential learning process, to assist the students in internalizing disaster knowledge in order for them to be able to apply the principles and develop the characters and competencies needed when disasters occur. The implementation of the program has resulted in the compilation of creative and innovative disaster education learning packages that meet the needs and characteristics of students, namely posters, poems, short stories, videos, and dances.